GIANT CELL GRANULOMA OF THE MAXILLA - Uzbek, Usman Haider; Mushtaq, Iram (Journal of Ayub Medical College Abbottabad, 2007)
The case report is of a 30 year old male, who complained of a slowly expanding swelling in the maxilla in the left premolar region. The swelling was clinically and radiographically diagnosed as Central Giant Cell Granuloma. The patient also had Angles Class2 Division 2 Malocclusion in which repeated micro trauma may have possibly contributed to the formation of the tumor. The tumor was surgically removed under general anesthesia followed by local injections of corticosteroids. Keywords: Giant cell granuloma,Maxilla,Benign Lesion, Surgical Excision, Corticosteroid Injection, Unusual Etiology